Simultaneous and accurate visual identification of chicken, duck and pork components with the molecular amplification integrated lateral flow strip. (1st March 2021) - Qin, Panzhu; Xu, Jianguo; Yao, Li; Wu, Qian; Yan, Chao; Lu, Jianfeng; Yao, Bangben; Liu, Guodong; Chen, Wei
Highlights: Integration of mPCR and LFS for simultaneous screen of multiple adulterations. Simultaneous mPCR is optimized based on the designed functional primer sets. Multiple amplicons can be simultaneously distinguished with the same LFS. More than 40 various processed beef are well authenticated with this mPCR-LFS. Application of molecular protocols can be widened in the resource-limited setups. Abstract: We propose a visual strategy for simultaneous detection of multiple adulterated components in beef by integration of multiple polymerase chain reaction (mPCR) with the lateral flow strip (LFS). The primer sets for adulterated components are uniquely designed with different nucleic acid tags (NAT), enabling the amplicons with specific wobbled sequences at two opposite ends. The wobbled sequences will precisely hybridize with the pre-immobilized capture probes on T lines (T1, T2 and T3) and C line, contributing to the coloration of LFS. Taking advantages of extraordinary amplification efficiency of PCR and simplicity of LFS, common adulterated components including chicken, duck and pork can be easily detected with LOD as low as 0.01% (wt%), which is comparable to that of quantitative real-time polymerase chain reaction (qPCR) but with more simplified operations and reduced costs. The method can be extended to identification of other components by replacing the functional primer set. This method can be a useful candidate for meat quality control at the resource-limited setups.